Family Care Therapy (FaCe-T) Based on Application Nutritional Status of Picky Eater - Maya Cobalt Angio Septianingtyas; Rusmiyati Rusmiyati; Tia Nurhanifah (Indonesian Journal of Global Health Research, 2025)
Toddler nutrition problems are important health problems that must be addressed immediately. Because at the age of toddlers, the development process is very rapid and has an impact on the future life of toddlers. The high number of toddlers who experience nutritional problems is the task of health workers and all levels of society, especially families. One of the nutritional problems that toddlers often experience is picky eating. Picky eating is an eating disorder that usually occurs in children in the form of liking to choose food, only consuming certain foods and vomiting food that has entered the mouth. If allowed to continue, this condition can cause nutritional imbalances in the body and malnutrition. Based on previous research, parenting patterns are closely related to the incidence of picky eating in toddlers. Therefore, optimizing family involvement is very important in handling picky eating toddlers. Family Care Therapy (FaCe-T) is an intervention carried out by the family (mother) with an ethical humanist approach, namely providing treatment to toddlers with full affection, attention, gentleness and sincerity with the aim of changing the behavior or eating habits of toddlers. The role of the family is crucial in managing toddlers with picky eating habits. The family is the primary caregiver, often interacting with the child, being closest to them, and understanding their needs. This is why the family’s parenting style is so important in addressing picky eating in toddlers. A positive parenting approach can have a beneficial impact on the child. Therefore, an intervention may be necessary to help change the family's parenting practices. Objective: This study aims to determine the effect of family care therapy (Face-T) on nutritional status in picky eater toddlers. Method: This study uses a quasi-experimental research design, with a one group pre and post test design with control design. The population in this study consists of all mothers with toddlers in the working area of Krobokan Health Center, Semarang. The sample size in this study is 77. The sampling technique used in this study is purposive sampling. Results: The results of the analysis test on respondents obtained a p-value of 0.001, this value is proven to be smaller than the p-value of 0.05, so Ha is accepted and Ho is rejected, which means that there is an influence of humanistic Family Care Therapy (FaCe-T) by utilizing applications on improving the nutritional status of picky eater toddlers. Conclusions: The conclusion of this study is family care therapy (FaCe-T) is effective in improving the nutritional status of toddlers who are picky eaters.